THE ORGANIZATION OF SPACE AND EDUCATION SCHOOL-TIME: ANALYSIS OF AN INTEGRAL EDUCATION EXPERIENCE - Marília Andrade Torales Campos; Veronica Branco; Leziany Silveira Daniel (Editora da Universidade de Santa Cruz do Sul, 2016)
This article proposes a reflection upon the public policies in education with regard to the experiences on full-time education - more specifically, on the process of extension and use of school-educational time, carried out in Apucarana/PR. The choice of this research object is justified by the emergence of a new political-economic reality in the country, which imposes the need to rethink school and its social functions. Thus, from the analyzed experience, the emergence of a new concept of school was noticed. This concept is based on a communitarian structure, or on learning communities, and it transcends the classic teacher-student dichotomy, including new learning-teaching individuals. In order to understand the data, it is important to rethink the meaning of time and space, not only in school, but also in families and communities from the social context.